The role of technological innovation in global climate policy - Chenyu Wang (Research in Globalization, 2021)
This research builds a dynamic model of the global economy and climate with three endogenous knowledge stocks. We confirm that the contribution of induced R&D in global climate change is shown to be very sensitive to the elasticity of substitution between energy and other factors of production since growth patterns of all types of research depend on whether inputs are gross complements or gross substitutes. The second, the duplication externality. Induced R&D generates a lower abatement cost reduction if we externalize duplication in the business as usual scenario. Third, the initial level of research expenditure. Higher initial levels of energy-related R&D shares would create a market size effect, leading to an increased contribution of induced R&D. Fourth, the inter-firm knowledge spillovers. Firms are not successful in capturing all the benefits they create, as many benefits flow out into other firms free of charge. These benefits are called inter-firm knowledge spillovers. Fifth, first-best and second-best policies. The first-best policy fully internalizes the inter-firm knowledge spillovers, which leads to increases in the levels of all types of research, whereas the second-best policy does not internalize it, which leads to induced changes in research resulting from the carbon tax affecting pre-existing market distortions. Sixth, a research dividend effect and tax burden effect. The tax may induce an increase in research expenditure, which would increase the welfare and consumption levels. Finally, the results demonstrated that induced R&D has a limited role in the abatement cost reduction of carbon emissions overall.
Keywords: 330; Environmental economics; Economic modelling; Global climate policy; R&D Investments; Technological innovation